Flexible all-solid-state asymmetric supercapacitor assembled using coaxial NiMoO4 nanowire arrays with chemically integrated conductive coating†. (1st October 2015) - Chen, Yaping; Liu, Borui; Liu, Qi; Wang, Jun; Liu, Jingyuan; Zhang, Hongsen; Hu, Songxia; Jing, Xiaoyan
Graphical Abstract: The one-dimensional (1D) nanostructured NiMoO4 on highly conductive carbon cloth (CC) improve the supercapacitor performance by enhancing the structural integrity and electrical oneness of the MOs-based electrode. Meanwhile, a flexible all-solid-state asymmetric supercapacitor (ASC) employing NiMoO4 /PANI and commercial active carbon (AC) as the positive and negative electrodes, respectively, delivers a maximum specific energy of 99.26 Wh Kg −1 and a maximum specific power of 10667 WbKg −1 . Meanwhile, the ASC device demonstrates highly stable cyclic performance with outstanding robust flexibility. Highlights: NiMoO4 nanowires on carbon cloth improve cyclic stability and rate capability. The NiMoO4 /PANI electrode exhibits a high areal specific capacitance. NiMoO4 /PANI electrode achieves excellent electrochemical stability. The flexible supercapacitor device demonstrates excellent output power. Abstract: In this work, we synthesized radially developed metal oxides (MOs) array of one-dimensional (1D) nanostructured NiMoO4 on highly conductive carbon cloth (CC) and put forward an effective strategy to greatly improve the supercapacitor performance by enhancing the structural integrity and electrical oneness of the MO-based electrode. The hybrid NiMoO4 / polyaniline (PANI) electrode exhibits a high areal specific capacitance of ca. 1.34 F cm −2 (1340 F g −1 ) at a current density of 1 mA cm −2 . In comparison, the pristine NiMoO4 nanowires (NWs) have a specific capacitance of ca. 1.142 F cm −2 (1142 F g −1 ) at the same current density. An outstanding capacitance retention for NiMoO4 /PANI hybrid nanowire electrodes has been achieved (ca. 96.7% after 2000 cycles with an average coulombic efficiency of over 99.5%), which is superior to pure NiMoO4 (ca. 81% after 2000 cycles). Moreover, a flexible all-solid-state asymmetric supercapacitor (ASC) employing NiMoO4 /PANI and commercial active carbon (AC) as the positive and negative electrodes, respectively, delivers a maximum specific energy of 99.26 Wh Kg −1 (297.78 mWh cm −2 ) and a maximum specific power of 10667 W Kg −1 (32.04 mW cm −2 ). In addition, the ASC device demonstrates highly stable cyclic performance with outstanding and robust flexibility.